2021
DOI: 10.3390/ijms22126375
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Progenitor Cell-Derived Extracellular Vesicles: Potential Therapeutic Application in Tissue Repair and Regeneration

Abstract: Recently, many studies investigated the role of a specific type of stem cell named the endothelial progenitor cell (EPC) in tissue regeneration and repair. EPCs represent a heterogeneous population of mononuclear cells resident in the adult bone marrow. EPCs can migrate and differentiate in injured sites or act in a paracrine way. Among the EPCs’ secretome, extracellular vesicles (EVs) gained relevance due to their possible use for cell-free biological therapy. They are more biocompatible, less immunogenic, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 126 publications
0
28
0
Order By: Relevance
“…Of note, inflammatory activation of cells with recombinant low-dose TNFα strongly amplified expression and secretion of CXCL12 in SMCs and EPCs. As we have previously observed that EPC-derived microvesicles (MVs, also known as microparticles or extracellular vesicles) alone may modulate key functions of SMCs and as MVs harbor and transfer bioactive substances including chemokines and microRNAs [ 20 , 21 , 22 ], we also evaluated the presence of CXCL12 in MVs. Indeed, a notable amount of CXCL12 could be identified in MVs derived from EPCs (EPC-MV) and SMCs (SMC-MV), indicating that a relevant portion of released CXLC12 is transferred to MVs ( Figure 1 C).…”
Section: Resultsmentioning
confidence: 99%
“…Of note, inflammatory activation of cells with recombinant low-dose TNFα strongly amplified expression and secretion of CXCL12 in SMCs and EPCs. As we have previously observed that EPC-derived microvesicles (MVs, also known as microparticles or extracellular vesicles) alone may modulate key functions of SMCs and as MVs harbor and transfer bioactive substances including chemokines and microRNAs [ 20 , 21 , 22 ], we also evaluated the presence of CXCL12 in MVs. Indeed, a notable amount of CXCL12 could be identified in MVs derived from EPCs (EPC-MV) and SMCs (SMC-MV), indicating that a relevant portion of released CXLC12 is transferred to MVs ( Figure 1 C).…”
Section: Resultsmentioning
confidence: 99%
“…Beyond the proven beneficial outcomes with the MSCderived EV treatment in experimental animal models of stroke (34)(35)(36)(37)(38)(39), many aspects are yet to be resolved about the production of EVs for their use in clinical practice, such us large-scale production, conditions in different physiologically environments, and standardized experimental protocol for extracting EVs to provide batch uniformity according to GMP regulations (40,48,49).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they do not have an oncologic risk or a risk of permanent engraftment or transformation. Finally, their low immunogenic potential allows a possible allogeneic use, making it easier to develop off-the-shelf products [93]. However, the main limitation of the use of ADSC-derived EVs consists in the production upscaling.…”
Section: Advantages and Limitations Of Therapeutic Approaches Using Adsc And Adsc-evmentioning
confidence: 99%